2003
DOI: 10.1021/la0268653
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Microelectrophoresis Studies of the Rutile/Aqueous Solution Interface

Abstract: A recently developed high temperature microelectrophoresis cell was employed for ζ-potential measurements at the rutile/aqueous solution interface over a wide range of pH at temperatures of 25, 120, and 200 °C. Water, 0.001 mol kg -1 NaCl(aq), and 0.01 mol kg -1 NaCl(aq) solutions were tested at these temperatures. The desired pH values were attained by adding either HCl(aq) or NaOH(aq). The obtained experimental data allowed us to estimate isoelectric point pH values (pHiep) of 5.26 ((0.45) at 25 °C, 5.13 ((0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 28 publications
4
61
0
Order By: Relevance
“…For this particular rutile sample, a pH PPZC around pH 5.4 is well established in the literature (Machesky et al, 1998;Ridley et al, 2002;Fedkin et al, 2003) and was also confirmed during our previous potentiometric titration study (Jonsson et al, 2009). In the latter study, we established the point of zero salt effect (pH PZSE ) of rutile in NaCl solutions as 5.37 (±0.1), which was used to estimate the pristine point of zero charge, pH PPZC = 5.4 (±0.1) with the relation…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…For this particular rutile sample, a pH PPZC around pH 5.4 is well established in the literature (Machesky et al, 1998;Ridley et al, 2002;Fedkin et al, 2003) and was also confirmed during our previous potentiometric titration study (Jonsson et al, 2009). In the latter study, we established the point of zero salt effect (pH PZSE ) of rutile in NaCl solutions as 5.37 (±0.1), which was used to estimate the pristine point of zero charge, pH PPZC = 5.4 (±0.1) with the relation…”
Section: Methodssupporting
confidence: 84%
“…In a parallel study, we will be reporting ATR-FTIR spectroscopic measurements of both aspartate and glutamate on rutile together with theoretical molecular calculations on these systems. We focused on rutile in the present study because it is a model colloidal substance: identically prepared rutile samples have been the subject of numerous intensive studies of proton and cation adsorption (Machesky et al, 1998;Ridley et al, 1999Ridley et al, , 2004Ridley et al, , 2005Fedkin et al, 2003;Zhang et al, 2004). Rutile was also probably present on the prebiotic Earth , which makes it relevant to origin of life studies.…”
Section: Introductionmentioning
confidence: 99%
“…4). These results are in the range of experimental measurements at titania-water interfaces [46]. In particular, recent experimental measurements of zeta potentials of (non-spherical) titania nanoparticles with characteristic diameters of 30-40 nm in ultra-pure water at room temperature were 34 mV in magnitude [47], and the current estimated values are also in that range.…”
Section: Resultssupporting
confidence: 55%
“…This simplified approach fails to describe the TiO 2 ζ values obtained in this study although the trend of the ionic strength effect could be predicted. The second way to calculate the ζ potential is based on the empirical distance between the slip ζ plane and the head end of the diffuse layer by the following equation [43]:…”
Section: Charge Behavior Of Tiomentioning
confidence: 99%